2000
DOI: 10.1007/s004150070094
|View full text |Cite
|
Sign up to set email alerts
|

A prevalence study of primary dystonia in eight European countries

Abstract: There have been few epidemiological studies of dystonia. Most previous studies have provided estimates based on few cases. A European prevalence study was undertaken to provide more precise rates of dystonia by pooling data from eight European countries. Diagnosed cases were ascertained by adult neurologists with specialist movement disorder (and botulinum toxin) clinics. The crude annual period prevalence rate (1996-1997) for primary dystonia was 152 per million (95% confidence interval 142-162), with focal d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
87
8

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 315 publications
(99 citation statements)
references
References 15 publications
4
87
8
Order By: Relevance
“…Jedynak et al [6], in their prospective study of 65 patients of WC in European population also reported that the mean age of onset of WC was 36.3 ± 12. The Epidemiological Study of Dystonia in Europe (ESDE) Collaborative Group in their prevalence study of dystonia in Europe, reported WC to be more prominent in the 50-59 years age group [8]. However, this report did not mention the duration of WC in this population, which precludes any information on the age of onset of WC.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Jedynak et al [6], in their prospective study of 65 patients of WC in European population also reported that the mean age of onset of WC was 36.3 ± 12. The Epidemiological Study of Dystonia in Europe (ESDE) Collaborative Group in their prevalence study of dystonia in Europe, reported WC to be more prominent in the 50-59 years age group [8]. However, this report did not mention the duration of WC in this population, which precludes any information on the age of onset of WC.…”
Section: Discussionmentioning
confidence: 56%
“…Demographic and clinical characteristics of WC have been previously reported either by studies exclusively reporting on WC [5,6] or by studies highlighting the characteristics of the focal task-specific hand dystonias where some patients had WC [7,8] (table 2). In this study on Indian population, we report the clinical characteristics of a large cohort of patients with WC.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of CD in the general population is estimated to vary from 0.006% from a clinic-based study in eight European countries to 0.4% in the US", based on a consumer database survey [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…CD remains the most common of the focal dystonias [3,5]. Classiications of CD include torticollis (turning or rotation of the head towards one side); laterocollis (tilting of the head towards one side); anterocollis (head and neck lexion); and retrocollis (head and neck extension) or a combination of these movements [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…27 Outside of the United States, the prevalence of individuals with pri-mary focal dystonia who presented to outpatient clinics ranges between 61 and 137 per million persons. 9,11,16,26,31 Whereas primary focal dystonia is relatively rare, task-specific lower extremity dystonia is even less prevalent. Within a specialized movement-disorder clinic, only 4 (0.7%) of 579 individuals with primary focal dystonia had lower extremity dystonia, 21 and none of these individuals presented with the specific movement pattern described in this case.…”
mentioning
confidence: 99%